Patogenicidade de isolados de Sclerotinia sclerotiorum sobre germoplasma de soja - Guerra, Renato Carnellosso (2017)
The White mold or Sclerotinia stem rot, caused by the fungus Sclerotinia sclerotiorum, has become a serious problem in soybean production areas. The objectives of this work were to evaluate whether in different agricultural regions of Brazil, the fungus S.sclerotiorum, has a behavioral similarity at the level of symptoms on certain soybean genotypes, to evaluate which genotypes can be used for each region and which materials can be used for plant breeding. The experiment was conducted at the University of Santa Maria, in a growth chamber with controlled temperature and humidity, between November 2016 and February 2017, with three isolated of S.sclerotiorum, collected in the cities of Itaara and Passo Fundo in Rio Grande do sul and Jataí in Goias, in the season of 2015/2016, on a total number of 56 soybean genotypes. The inoculation of the isolates was performed by the straw test method when the plants were in the growth stages V3/V4. For all genotypes, it was evaluated average lesion size, in centimeters, five days after inoculation. Each treatment was consisted of seven replications, each replication being one plant. Analyzes resulted in the formation of four symptom levels, being susceptible, intermediate, moderately resistant and resistant. Analyzes demonstraded that for the three isolates, different resistant reaction levels were obtained for the tested genotypes. It was verified that the isolate of Passo Fundo - RS, showed resistant pattern the genotype CD 2655 and as susceptible patterns, five genotypes. For the reaction to the Itaara - RS isolate, there were no resistant reactions and nine genotypes were susceptible. For the isolate from Jatai - GO, six genotypes were resistant and one susceptible, NS4823. The use of the UPGMA grouping method, created for each isolate, showed no correlation emphasizing that the isolates have genetic diversity.